Alterations of Gut Microbiota and Blood Lipidome in Gestational Diabetes Mellitus With Hyperlipidemia - Liu, He; Pan, Li-Long; Lv, Siting; Yang, Qin; Zhang, Hao; Chen, Wei; Lv, Zhuwu; Sun, Jia (Frontiers in Physiology, 2019)
Clinical gestational diabetes mellitus (GDM) is frequently associated with hyperlipidemia comorbidity. Altered human gut microbiome has been linked to GDM and hyperlipidemia respectively but not the comorbid condition. We hypothesize that the occurrence of hyperlipidemia with GDM may be characterized by distinguishable gut microbiome and blood metabolomic patterns. We presented comprehensive microbiomic coupled with lipidomics analyses to characterize gut microbiota and lipometabolism of plasma samples in women with gestational diabetes mellitus only, hyperlipidemia only and those with diabetes plus hyperlipidemia, and to explore association of the gut microbiota composition with blood lipid profiles and clinical parameters of gestational diabetes with or without commodity. We found that the relative abundance of bacterial taxa Streptococcus, Faecalibacterium, Veillonella, Prevotella, Haemophilus and Actinomyces was significantly higher in diabetes plus hyperlipidemia cohorts. Moreover, several bacteria were correlated with fasting plasma glucose and blood lipid levels of the participants with GDM and hyperlipidemia. The altered plasma lipidome in subjects with diabetes plus hyperlipidemia suggested that characteristic blood lipid profiles were associated with the pathogenesis of gestational diabetes plus hyperlipidemia. Collectively, this study provides insights on changes in fecal microbiota and plasma lipidome to predict and characterize the development of gestational diabetes with lipid metabolic abnormality.